2011
DOI: 10.1093/nar/gkr480
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the structural requirements for ATP hydrolysis and DNA cleavage by the EcoKI Type I DNA restriction and modification enzyme

Abstract: Type I DNA restriction/modification systems are oligomeric enzymes capable of switching between a methyltransferase function on hemimethylated host DNA and an endonuclease function on unmethylated foreign DNA. They have long been believed to not turnover as endonucleases with the enzyme becoming inactive after cleavage. Cleavage is preceded and followed by extensive ATP hydrolysis and DNA translocation. A role for dissociation of subunits to allow their reuse has been proposed for the EcoR124I enzyme. The EcoK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…It is important to note that, in the absence of ATP hydrolysis, EcoKI is a stable assembly containing all five protein subunits (Dryden et al 1997;Roberts et al 2011). However, for EcoR124I, the binding constants for each of the two HsdR differ by over two orders of magnitude (0.6 nM and 200 nM, respectively), and the two forms of the enzyme, R 1 M 2 S 1 and R 2 M 2 S 1 , are in dynamic equilibrium (Supplemental Material; Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that, in the absence of ATP hydrolysis, EcoKI is a stable assembly containing all five protein subunits (Dryden et al 1997;Roberts et al 2011). However, for EcoR124I, the binding constants for each of the two HsdR differ by over two orders of magnitude (0.6 nM and 200 nM, respectively), and the two forms of the enzyme, R 1 M 2 S 1 and R 2 M 2 S 1 , are in dynamic equilibrium (Supplemental Material; Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the direction of DNA translocation is defined in the chromatin remodeling translocase, it imposes a similar directionality on each HsdR, and since these have to pull DNA in toward the MTase core of the type I RM enzyme, the orientation of each HsdR relative to the MTase core becomes defined. Assuming that the DNA path between the DNA bound to the HsdR and the DNA bound to the core MTase must not be any longer than ;40 bp, as determined by DNA footprinting experiments (Mernagh et al 1998;Powell et al 1998) and the minimum length of 45 bp of DNA required for ATP hydrolysis (Roberts et al 2011), then the locations of the RecA-like motor domains of the HsdR are forced to be as shown, so that their DNA-binding sites are close to the DNA-binding site of the MTase core. Placement of the HsdR on either side of the MTase and interacting directly with DNA is further supported by the length of the structure of the ArdA anti-restriction DNA mimic protein (Nekrasov et al 2007;McMahon et al 2009), which occupies the entire DNA-binding site on type I RM enzymes.…”
Section: Atomic Modeling Of the Complete Rm Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent this burden, the organism appears to control the intracellular enzyme concentration. As shown for E. coli, efficient phage restriction occurs by using about 60 molecules of EcoKI, which would consume ϳ0.2% of the total ATP pool (86,87).…”
Section: Fitness Cost Incurred By R-m Systems On Host Bacteriamentioning
confidence: 99%
“…These results contradict those observed by Bianco and Hurley (29). Similar experiments with EcoKI have also found that RecBCD has no effect on turnover of the holoenzyme (45).
Figure 5.‘Turnover’ of EcoR124I MTase during DNA cleavage and translocation does not occur and is not influenced by the presence of the exonuclease activity of RecBCD.
…”
Section: Resultsmentioning
confidence: 64%